2002
DOI: 10.1191/0960327102ht248oa
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of a GM3 cancer vaccine inMacaca fascicularis monkey: a 12-month study

Abstract: GM3 is a ganglioside that has been biochemically identified as dominating the cell surface of several human tumours, but is also found on human normal cells at much lower density. Since GM3 is widely distributed in essentially all types of animal cells, there is a conflict with the concepts of tumour-associated antigen, immunogen, and toxicity. We have designed a GM3-based cancer vaccine for the treatment of human breast and melanoma tumours. Prior to the Phase I clinical trial, we carried out a 12-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…30 Tissue hardening and swelling at the immunization site had been previously observed in the preclinical studies in rats and monkeys with NAcGM3/VSSP/Montanide ISA 51 as vaccine or with the emulsion of Montanide ISA 51 as control. 31,32 However, it is difficult to clarify in this small clinical trial if the skin toxicity observed is only related with the oil adjuvant, or was increased with the NeuGcGM3/VSSP vaccine.…”
Section: Discussionmentioning
confidence: 93%
“…30 Tissue hardening and swelling at the immunization site had been previously observed in the preclinical studies in rats and monkeys with NAcGM3/VSSP/Montanide ISA 51 as vaccine or with the emulsion of Montanide ISA 51 as control. 31,32 However, it is difficult to clarify in this small clinical trial if the skin toxicity observed is only related with the oil adjuvant, or was increased with the NeuGcGM3/VSSP vaccine.…”
Section: Discussionmentioning
confidence: 93%
“…However, this finding has been also observed in rats and monkeys subject to episodically dosing of Montanide with rest periods between (Bada et al, 2002;Mancebo et al, 2012). In fact, gathering secondary reactions from 25 clinical trials representing more than 4000 patients and 40,000 injections has shown that Montanide ISA 51 adjuvant is well tolerated, but local reactions (mainly granuloma, local pain, tenderness and erythema) and general adverse event (flu like symptoms, nausea vomiting and pain) were often observed (Aucouturier et al, 2006).…”
Section: Daymentioning
confidence: 74%
“…Local damage at the administration site, observed in both adjuvant and vaccine treated animals, has been previously reported in assays performed with other cancer vaccines tested in our lab, in which Montanide ISA 51 was also used as adjuvant (Bada et al, 2002(Bada et al, , 2005Mancebo et al, 2012). Montanide ISA 51 is an oilbased adjuvant and these types of adjuvant are accused of producing local reactions such as abscesses and granulomas (Yamanaka et al, 1992;Leenaars et al, 1998;CERB, 2006).…”
Section: Daymentioning
confidence: 80%
“…The contribution of gangliosides to cell biology together with the NeuGc-GM3 ganglioside expression as tumorassociated antigen [22], and its limited toxicity as a targeted immunotherapy molecule [23,24], support its relevance for cancer control. Moreover, targeting the NeuGc-GM3 ganglioside by immunotherapeutic approaches may promote [6,25].…”
Section: Discussionmentioning
confidence: 99%